I know that - Loves, June (Singapore : SRA Macmillan/McGraw-Hill, 1994)
A smartypants girl, who thinks she know everything about the dangerous animals she meets, comes to an untimely end.
Keywords: Animals--Fiction; Pride and vanity--Fiction